Вплив розчинів нанометалів на інтенсивність окисно- відновних процесів при зберіганні плодів груші. - Сердюк, Марина Єгорівна; Кюрчева, Людмила Миколаївна; Андрущенко, Микола Васильович; Жукова, В. Ф (Мелітополь, ТДАТУ, 2019)
UKR: Дослідження присвячені вивченню та науковому обґрунтуванню впливу розчинів нанометалів на інтенсивність окисно-відновних процесів у плодах груші протягом тривалого зберігання. В результаті досліджень встановлено, що обробка розчинами нанометалів сприяла стабілізації інтенсивності дихання плодів на рівні 20 мг СО2 кг/год протягом всього періоду зберігання. Незначне підвищення інтенсивності дихання (у 1,3 рази) було зафіксовано на 180 добу зберігання плодів груші сорту Киргизька зимова за обробки 60 відсотковим розчином нанометалів (варіант1). Поряд з цим, у плодах контрольного варіанту спостерігалося клімактеричне зростання дихання на 90…120 добу зберігання. Визначено, що середні втрати титрованих кислот у плодах контрольних варіантів становили 70 %, а цукрів 58% від початкового значення. Обробка плодів розчинами нанометалів зменшувала середній рівень втрат титрованих кислот протягом періоду зберігання в середньому на 23%, загального цукру на 6%, сахарози – на 8%. Показано, що післязбиральна обробка розчинами нанометалів сприяла формуванню більш гармонійного смаку плодів груші різних помологічних сортів протягом періоду зберіганню.///////////////////// ENG: Researches are devoted to the study and scientific substantiation of the influence of solutions of nanometals on the intensity of oxidative-reduction processes in the fruit of the pear during the long-term storage. To store fruits, pears were harvested when the ergonomic degree of ripeness reached, typical in shape and color. Inspection, sorting and calibration of the fruit were carried out prior to storage. The treatment of products with solutions of nanometals was carried out in the preparatory compartment of the storage with forced cooling. The fruits were loaded into baths with working solutions of nanometals. After drying, the fruits were packed in containers. At the same time, the pears were arranged diagonally, guiding the fistula in the intervals between the fruits of the next row. Treatment options: control - fruit pears without processing; option 1: 60% nanometal solution which consists of Ag and Mg; Option 2: 1 percent solution of nanometals which consists of Ag and Mg. In addition to nanometals, glycerol, propylene glycol and water were included in the working solutions. Pear fruit storage was carried out in a refrigerating chamber at a temperature of 0 ± 2 ° С, relative humidity of 95%. As a result of the research, it was found that treatment with nanometal solutions contributed to stabilizing the intensity of the respiration of the fruits at a level of 20 mg СО2 kg / h during the whole period of storage. A slight increase in the intensity of respiration (1.3 times) was recorded for 180 days of storage of pears of the Kyrgyz winter variety when treated with 60% nanometal (option 1). Along with this, in the fetuses of the control variant, the climacteric growth of respiration was observed for 90 ... 120 days of storage. It was determined that the average loss of titratable acids in fruits of control variants was 70%, and sugars were 58% of the initial value. Fruit treatment with nanometal solutions reduced the average loss of titratable acids by 23% on average during the storage period, and by 6% in total sugars and sucrose by 8%. In this case, within the same grade, the specified level of loss was almost the same and did not change statistically depending on the variant of processing. It was shown that post harvest treatment with nanometal solutions contributed to the formation of a more harmonious taste of the pears of different pomological varieties during storage.
INFLUENCE OF NANOMETAL SOLUTIONS ON THE INTENSITY OF OXIDATION-REDUCTION PROCESSES IN THE STORAGE OF PEAR FRUIT
Keywords: плоди груші; інтенсивність дихання; титрована кислотність; цукри; зберігання; цукрово-кислотний індекс; pear fruits; respiration rate; titratable acidity; sugars; sugar-acid index; taste; storage